Preventive measures and perceived challenges in delivering oral health care for elderly patients: a survey of dental hygienists in Norway - Anne Breivik; Simen E. Kopperud; Qalbi Khan; Aida Mulic; Linda Stein (Acta Odontologica Scandinavica)
Objective: This study aimed to gain knowledge of general oral health preventive measures with a specific focus on root caries preventive measures for patients ≥65 years old, performed by Norwegian dental hygienists in public and private dental health services. A secondary aim was to investigate differences and challenges in prevention practices.